Cyclic 3′,5′-Adenosine Monophosphate Phosphodiesterase of Escherichia coli - Nielsen, L. D. (1973)
The cyclic 3′,5′-adenosine monophosphate (c-AMP) phosphodiesterase from Escherichia coli has been partially purified. The enzyme has an apparent molecular weight of 30,000, a Michaelis constant of 0.5 mM c-AMP, and a pH optimum of 7. The partially purified enzyme requires for activity the presence of a reducing compound and of either iron or a protein which seemingly acts as iron carrier.